Engineered charge transport layers for improving indoor perovskite photovoltaic performance - Ram Datt (Journal of Physics: Energy, 2024)
The developing Internet of Things market is attracting the indoor photovoltaic (IPV) as an essential power source. Perovskite photovoltaics (PPVs) are a fascinating candidate for IPV in solution-processable photovoltaics. Recent developments in PPVs can deliver power conversion efficiency (PCE) up to 25% outdoor (AM 1.5 G) and over 40% under indoor (1000 lux) light. The selection of charge transport layers (CTLs) has played an essential role in improving PPVs indoor performance. Herein, formamidinium-caesium-based mixed-cation (FACsPb(I,Br)3) PPV devices are fabricated, and evaluated their outdoor and indoor performances by changing the different CTL combinations such as PTAA-PCBM and SAM-C60. Outdoor PCEs were 13.76% and 15.27% achieved for PTAA-PCBM and SAM-C60-based devices, respectively. Meanwhile, under LED (4000 K) 1000 lux, the PCEs were 26.32% and 31.92% for PTAA-PCBM and SAM-C60-based PPV, respectively. The short circuit current (Jsc) (116.8–122.5 µA cm−2) and fill factor (FF) (0.724–0.817) were the main parameters which improved for SAM-C60-based devices under indoor light. This study points to the importance of CTL combination and indicates the promising potential of SAM-C60 interlayers in PPV indoor applications.